AUTHOR’S DIGITAL VIDEO: CREATING AND USING FOR THE LEARNING - Igor V. Riatshentcev; Viacheslav A. Starodubtsev (Открытое образование (Москва), 2016)
The article considers the functionality of software to construct the author’s video for its use in distance learning and its audiovisual implementation in the open educational space.